Analisa Kepuasan Pelanggan Bandar Udara Hang Nadim Batam - Rusda Irawati; Aditya Wirangga; Shinta Wahyu Hati (Politeknik Negeri Batam, 2012)
Performance measurement of airport BP Batam as the only airport in Batam, comprehensively and continuously need to continue to do so that the parties can know the condition of the Airport management achievement of its performance, evaluate and subsequently a chance to take a strategic decision as well as operational in order to create improved service and performance improvements in the future.The purpose and objective of this research are: (1) To know the influence of the quality of the service for customers satisfaction at the airport Hang Nadim Batam, (2) to know the levels of customers satisfaction at the airport Hang Nadim Batam. From the results of data processing using regression analysis , get the conclusion that, the biggest impact on customer satisfaction is derived from dimension Reliability, Assurance, Tangible, Emphaty and Responsiveness. The influence of service quality on customer satisfaction was at 48 %, and other factors beyond the quality of the service, an influential amounting to 52 %. There is a direct relationship between significant variable quality of service with customer satisfaction, on average 77% declare satisfied, with the sequence of service quality is responsivenes ( 85 % ) , tangible ( 80 % ) , reliability ( 80 % ) , assurance ( 78 % ), and empaty ( 73 % ). Generally average the satisfaction of passengers and users bandara Hang Nadim , was in the category of 3 ( quite satisfied ). Interval in this category is at the level of 0.75 to 0.99